LINGUOCULTUROLOGY AS A CULTURAL PHENOMENON OF LINGUISTICS - Nasirdinov Oybek (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In this article, main features and characteristics of discourse as a linguistic phenomenon are explained. Also, it reflects particular notions about discourse matters as a communicative process including anthropocentrism approach.